Al poeta ed amico Alois Gradnik per le sue spighe di grano questi fili d'erba Alojz Gradnik in Ada Negri - Toroš, Ana (Slavistična revija, 2010)
The article illuminates the reception of the Italian poet and writer Ada Negri in the Slovene lands in the first half of the 20th century, particularly the literary contatcs between Ada Negri and the Slovene poet and translator Alojz Gradnik. the study is large part based on the correspondence between the two authors in the 1930s.
Keywords: 20.st.; Gradnik, Alojz, 1882-1967; italijanska književnost; italijanske pesnice; literarni stiki; Negri, Ada, 1870-1945; pisma; prevajanje; Slovene literature; slovenska književnost; slovenski pesniki; translation